Gay Bombay : globalization, love and (be)longing in contemporary India - Shahani, Parmesh (SAGE Publications, 2008)
Through a multi-sited ethnography in an online-offline community, Parmesh Shahani examines how Internet technologies, the media industry, audiences and broader socio-historical contexts shape gay identity in contemporary urban India. He realizes that the identity of a gay man in the community is negotiated on the stability of the idea of Indianness. For readers across the world focused on India, Gay Bombay will serve as a memorable journey through various transitions in urban India.